Composition optimization of PLA/PPC/HNT nanocomposites for mandibular fixation plate using single-factor experimental design - Mohamed Haneef, Intan Najwa Humaira; Buys, Yose Fachmi; Shaffiar, Norhashimah; Abdul Hamid, Abd. Malek; Syed Shaharuddin, Sharifah Imihezri; Fitriani, Fitriani (Elsevier, 2022)
The need to overcome the secondary surgery to remove implanted metal fixation plate leads to the idea of replacing the material with degradable bionanocomposite. In this research, polylactic acid/polypropylene (PLA/PPC) blends incorporated with halloysite nanotubes (HNT) (0–6 wt %) were considered as the candidate material for mandibular fixation plate. A single-factor design using Design Expert software was used to determine 20 different compositions of PLA/PPC/HNT nanocomposites and their mechanical properties were then measured. The optimization of the PLA/PPC/HNT nanocomposite composition was performed based on the nanocomposite’s response to Young’s modulus, tensile strength, and elongation at break. Further analysis suggested an optimum composition of 92.5/7.5 PLA/PPC with 6 wt % of HNT. The statistical results predicted that there was a 71.7% possibility that the proposed nanocomposite would have the following mechanical properties: Young’s modulus of 2.18 GPa, a tensile strength of 64.16 MPa, and an elongation at break of 106.53%.